2011
DOI: 10.14236/jhi.v19i2.799
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients with neuropathic pain using electronic primary care records

Abstract: Background Chronic neuropathic pain is a common condition which is challenging to treat. Many people with neuropathic pain are managed in the community, so primary care records may allow more appropriate subjects to be recruited for clinical studies. Objective We investigated whether primary care records can be used to identify patients with diseases associated with neuropathic pain. Method We analysed demographic, diagnostic and prescribing data from over 100 000 primary care electronic patient records in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Neuropathic pain is a global burden. In a systematic review, van Hecke et al (2014) found that the worldwide prevalence of chronic NeP varied extensively, ranging from 1.3% (Gajria et al, 2011) to 17.9% (Toth et al, 2009). Such variation is likely because of not only the disparate areas in which the investigations were conducted but also the different sociodemographic characteristics, methods of data collection, and definitions of CP.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain is a global burden. In a systematic review, van Hecke et al (2014) found that the worldwide prevalence of chronic NeP varied extensively, ranging from 1.3% (Gajria et al, 2011) to 17.9% (Toth et al, 2009). Such variation is likely because of not only the disparate areas in which the investigations were conducted but also the different sociodemographic characteristics, methods of data collection, and definitions of CP.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless our findings are consistent with a review of over 100,000 electronic medical records in a primary care clinic where black patients were less likely to be diagnosed with neuropathic pain than their white counterparts. 23 Again, these findings should be interpreted cautiously, since data were not separated by gender and the prevalence of neuropathic pain was low in both the black and white groups. Quantitative sensory testing, which has been performed in women with PVD, 24 should be further studied by evaluating ethnic differences in pain perception.…”
Section: Discussionmentioning
confidence: 88%
“…As mentioned before, NeP appears to be better documented than PN; therefore, more epidemiological studies on the prevalence of NeP than of PN are available. While Bouhassira et al reported an overall prevalence of chronic pain with neuropathic characteristics in 6.9% of over 23,000 participants from France [25], Gajria et al found diagnoses associated with NeP in only 1.3% of over 100,000 primary care electronic records from London, UK [26]. For Japan, a cross-sectional, population-based epidemiological survey with more than 5,000 respondents led to a NeP prevalence of 3.2% [27].…”
Section: Resultsmentioning
confidence: 99%